The Influence of Right Ventricular Pacing Location, Pacing Burden and Paced QRS Duration to Subclinical Left Ventricular Systolic Dysfunction as Shown by Global Longitudinal Strain Echocardiography - Mohammad Iqbal; Gadih Ranti Endamatriza; Irene Lampita; Sindy Hendrawansyah; Sidhi Laksono; Melawati Hasan; Chaerul Achmad; Giky Karwiky; Hanna Goenawan; Mohammad Rizki Akbar; Arief Sjamsulaksan Kartasasmita (Acta Medica Indonesiana, 2021)
Background: Prolonged pacing of the right ventricle (RV) is associated with left ventricular (LV) systolic dysfunction. Several studies have shown that the RV pacing location, pacing burden (percentage), and paced QRS duration may affect LV systolic function. Subclinical LV dysfunction may occur early after implantation of a permanent pacemaker (PPM). Therefore, this study aims to detect early subclinical LV systolic dysfunction measured by global longitudinal strain (GLS) using speckle tracking echocardiography (STE) at one month after PPM implantation. Methods: A single-center, prospective cohort study was conducted, and all patients indicated for PPM implantation with preserved LV systolic function were included. Data of RV pacing location (RV apical vs right ventricular outflow tract (RVOT), pacing burden (percentage) (≤40% vs >40%), and paced QRS duration (≤150 ms and >150 ms) were obtained. The change of GLS was also measured before and one month after PPM implantation (delta GLS). Results: 37 patients were enrolled in this study, which demonstrated significant difference between GLS before (-20.30 SD 3.38) and after (-16.93 SD 3.47) PPM implantation (p=<0.001). There were no significant difference in delta GLS either between patients with RV pacing location on RV apical vs RVOT ((2.30 (0.00–10.50) vs 2.95(0.10–8.30), p=0.648) or between patient with paced QRS duration ≤150ms vs >150ms ((1.70 (0.30–8.30) vs 3.45 (0.0–10.5)), p=0.266). Meanwhile, there was a significant difference of delta GLS between patients with pacing burden ≤40% vs >40% (Mean 1.92 SD 1.37 vs 3.98 SD 3.04), p=0.007). Further analysis found that pacing burden only affected the delta GLS in group with apical RV pacing (≤40% (1.58 SD 0.59) vs > 40% (4.67 SD 3.47), p = 0.008) and did not affect the delta GLS in group with RVOT pacing (≤40% (2.32 SD 1.98) vs > 40% (3.29 SD 2.48), p = 0.446). Conclusion: The pacing parameter, particularly pacing burden > 40% may induce the subclinical LV systolic dysfunction after one month of pacemaker implantation as shown by decline of GLS,  especially when the RV pacing location was placed on apical.